HANDLING OF PRESS CRIMES - Anwar, Alfiansyah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The purpose of this study is to outline the procedure of handling crimes committed by the press. This study was analyzed using qualitative description by conducting a literature study of the problems outlined. The results of this study revealed that the handling of crimes committed by the press has its own uniqueness compared to other criminal handling. While there is no special event law for law enforcement for press criminal cases, there are certain procedures that must be bypassed. Law enforcement, police, prosecutors, and judges—should pay attention to these unique procedures. The flow of handling of press crimes is the submission of rights of responsibility, complaints of the press council, complaints to the police, investigations, investigations, prosecutions, court hearings